HUBUNGAN PENGETAHUAN IBU HAMIL TENTANG NUTRISI DENGAN KEJADIAN ANEMIA DALAM KEHAMILAN DI PUSKESMAS HUTAIMBARU KECAMATAN PADANGSIDIMPUAN HUTAIMBARU TAHUN 2016 - Pohan, Rostina Afrida; Khalida, Winny (Jurnal Kesehatan Ilmiah Aufa Royhan, 2016)
One factor was the high incidence of anemia, the lack of knowledge of the signs, symptoms and the impact caused by anemia as a result if the individual is exposed to anemia She did not feel "sick".The purpose of this study was to determine relationship knowledge about nutrition of pregnant women with anemia in pregnancy in Puskesmas Hutaimbaru Padangsidimpuan Hutaimbaru sub-district 2016. This study used a descriptive correlation research method with cross sectional design. The population in the study population in this study were all pregnant women who visited the health center Hutaimbaru as many as 33 people using sampling techniques Purvosive sampling. Data were analyzed by chi-square test.The results showed that There is a relationship of knowledge about nutrition of pregnant women with anemia in pregnancy in Puskesmas Hutaimbaru Padangsidimpuan Hutaimbaru sub-district 2016, this is evidenced by the results of the chi-square test with p-value = 0.005Advice for pregnant women is expected to be more routine checkups for health workers and actively participating in counseling conducted by health officials to obtain information relating to nutrition during pregnancy